AKTIVITAS FOTO JURNALISTIK DI HARIAN DISWAY - Rebecca Sanjaya Hamidoyo; Safitri Riyanti (COMMUNITY OF RESEARCH LABORATORY SURABAYA, 2022)
Photography is an activity to capture the moment either in making news, making advertisements or other activities that can be done by everyone. With photos, we can get and convey information to others. Photography is divided into several types, some of them are food photography, human interest, landscape photography, street photography, commercial photography, photojournalism, etc. Photojournalism has an important role in the process of preparing news information. Photojournalism does not only focus on photographing an event, but can also be used to support the accuracy of information published to the media. The authors do photojournalism at Harian Disway as a photojournalist. Harian Disway itself is a media company that focuses on the field of mass media (online media and print media). During authors’s time as a photojournalist, the authors has carried out reporting activities assigned by the coverage coordinator. Being a photojournalist must know the moments that contain news value so that the published news is interested to read. The series of photojournalist activities at Harian Disway begins with listing the news that will be covered, the reporting process, editing and captioning photos and sending the results to the photo editor. The purpose of this research is to add references for further research. This study used descriptive qualitative method. The results of the data in this study were obtained from the interview process with several photo journalist.